South Africa’s Road Game To International Court Of Justice: An Agenda For International Peace And Security? - Braimah, Awaisu Imurana; Quarshie, Lawrence (NAS RA)
This paper interrogates and reflects on South Africa’s journey to the International Court of Justice (ICJ). The objective was to seek justice for the besieged Gazans by Israel in the occupied territory. While the war in Gaza is an exothermic reaction by Israel to Hamas’s brutal attack on October 7, 2023, the conduct of the war on Gaza has been the indiscriminate bombings, disproportionate, and collective punishment of civilians in the overcrowded enclave. Despite all attempts by the international community (e.g., UNSC, EU) to halt the Gaza onslaught, Israel has thus paid no heed to calls for a humanitarian ceasefire to ameliorate the suffering masses in the Gaza Strip.
Keywords: International Court of Justice; South Africa